Use of nuclear physics methods for investigation of short-range ordering and defects in iron based simulatuing alloys - Evstyukhina I.A.; Kolotushkin V.P.; Miloserdin V.Yu.; Rudakov S.G.; Stepanov S.V.; Udovsky A.L.; Chercastchenko M.V.; Funtikov Yu.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The changes of short range ordering and electron density were investigated by means of the nuclear gamma-resonance and the positron annihilation spectroscopies in model alloys containing tungsten, chromium, molybdenum, and vanadium used as dopants. The change of the short-range ordering parameter sign was detected in alloys containing vanadium. Different ordering was also observed in binary and ternary iron alloys. It was shown that dislocations were the main defects in these materials after rolling.